Doctrina multiplex, veritas una - Łukowski, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2014)
Coherent thoughts about the truth seem to be more difficult than about any other abstract concepts. According to some fundamental presuppositions, the truth should be one and in a sense unchangeable. On the other hand, even a simple observation suggests something opposite – the truth seems to be variable and relative and that is why given in some different, alternative forms. The paper deals with all the above mentioned problems and other relative ones concerning the truth. The entire discussion coincides with an ancient dictum being the title of the article